2013
DOI: 10.1111/acv.12033
|View full text |Cite
|
Sign up to set email alerts
|

There and back again? Combining habitat suitability modelling and connectivity analyses to assess a potential return of the otter to Switzerland

Abstract: After a steady decline in the early 20th century, several terrestrial carnivore species have recently recovered in Western Europe, either through reintroductions or natural recolonization. Because of the large space requirements of these species and potential conflicts with human activities, ensuring their recovery requires the implementation of conservation and management measures that address the environmental, landscape and social dimensions of the problem. Few examples exist of such integrated management. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 44 publications
(80 reference statements)
0
13
0
Order By: Relevance
“…In this context, species distribution models (hereafter SDMs) represent an important and potentially useful tool, commonly used in conservation and management planning of single species at local, national, regional, or continental levels (Puddu et al 2009;Cianfrani et al 2011Cianfrani et al , 2013Falcucci et al 2013). Previously published SDMs for Apennine brown bears have been calibrated over the entire bear activity period (Posillico et al 2004;Falcucci et al 2008Falcucci et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, species distribution models (hereafter SDMs) represent an important and potentially useful tool, commonly used in conservation and management planning of single species at local, national, regional, or continental levels (Puddu et al 2009;Cianfrani et al 2011Cianfrani et al , 2013Falcucci et al 2013). Previously published SDMs for Apennine brown bears have been calibrated over the entire bear activity period (Posillico et al 2004;Falcucci et al 2008Falcucci et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…in habitat suitability assessment), multicriteria methods offer tools for modelling expert knowledge. This study attempts to prove that expert knowledge (even when no other data is available) (Doswald et al 2007, Cianfrani et al 2013 can be used in order to generate a habitat suitability model; however, the model needs to be validated after the species reintroduction. The model can be validated by using indirect records of species presence or by using data obtained from the animals using GPS.…”
Section: Methodsmentioning
confidence: 99%
“…The integrated study of organisms at multiple behavioural and organisational levels and scales in space and time is a current frontier in ecology (McGarigal et al 2016;Yackulic & Ginsberg 2016). Similar combinations of habitat suitability and connectivity models to the one presented in this thesis have increasingly been applied to aid conservation decisions (Cianfrani et al 2013;Dickson et al 2013) and, more rarely, invasive species management (Stewart-Koster et al 2015). Yet, Glen et al (2013) suggested that 'integrated landscape approaches' based on metapopulation theory, connectivity models and spatial optimization are currently underutilized to inform applied biosecurity problems.…”
Section: Other Study Systems and Applicationsmentioning
confidence: 91%
“…Similar combinations of habitat suitability and connectivity models have been used to study mobile species' use of entire landscapes (Cianfrani et al 2013;Dickson et al 2013;StewartKoster et al 2015). In this thesis, I took a resource-based modelling approach (Hartemink et al 2015) -building on the ecological or behavioural factors influencing the spatial population patterns of feral pigsand applied models to two seasonal scenarios (wet and dry).…”
Section: Research Approachmentioning
confidence: 99%
See 1 more Smart Citation